Adenosine effects on inhibitory synaptic transmission and excitation–inhibition balance in the rat neocortex. (7th January 2015) - Zhang, Pei; Bannon, Nicholas M.; Ilin, Vladimir; Volgushev, Maxim; Chistiakova, Marina
<x xml:space="preserve">Abstract</x> Key points Adenosine might be the most widespread neuromodulator in the brain, but its effects on inhibitory transmission in the neocortex are not understood. Here we report that adenosine suppresses inhibitory transmission to layer 2/3 pyramidal neurons via activation of presynaptic A1 receptors. We present evidence for functional A2A receptors, which have a weak modulatory effect on the A1‐mediated suppression, at about 50% of inhibitory synapses at pyramidal neurons. Adenosine suppresses excitatory and inhibitory transmission to a different extent, and can change the excitation–inhibition balance at a set of synapses bidirectionally, but on average the balance was maintained during application of adenosine. These results suggest that changes of adenosine concentration may lead to differential modulation of excitatory–inhibitory balance in pyramidal neurons, and thus redistribution of local spotlights of activity in neocortical circuits, while preserving the balanced state of the whole network. Abstract Adenosine might be the most widespread neuromodulator in the brain: as a metabolite of ATP it is present in every neuron and glial cell. However, how adenosine affects operation of neurons and networks in the neocortex is poorly understood, mostly because modulation of inhibitory transmission by adenosine has been so little studied. To clarify adenosine's role at inhibitory synapses, and in excitation–inhibition balance in pyramidal neurons, we recorded pharmacologically isolated inhibitory responses, compound excitatory–inhibitory responses and spontaneous events in layer 2/3 pyramidal neurons in slices from rat visual cortex. We show that adenosine (1–150 μm) suppresses inhibitory transmission to these neurons in a concentration‐dependent and reversible manner. The suppression was mediated by presynaptic A1 receptors (A1Rs) because it was blocked by a selective A1 antagonist, DPCPX, and associated with changes of release indices: paired‐pulse ratio, inverse coefficient of variation and frequency of miniature events. At some synapses (12 out of 24) we found evidence for A2ARs: their blockade led to a small but significant increase of the magnitude of adenosine‐mediated suppression. This effect of A2AR blockade was not observed when A1Rs were blocked, suggesting that A2ARs do not have their own effect on transmission, but can modulate the A1R‐mediated suppression. At both excitatory and inhibitory synapses, the magnitude of A1R‐mediated suppression and A2AR–A1R interaction expressed high variability, suggesting high heterogeneity of synapses in the sensitivity to adenosine. Adenosine could change the balance between excitation and inhibition at a set of inputs to a neuron bidirectionally, towards excitation or towards inhibition. On average, however, these bidirectional changes cancelled each other, and the overall balance of excitation and inhibition was maintained during application of adenosine. These results suggest that changes of adenosine concentration may lead to differential modulation of excitatory–inhibitory balance in pyramidal neurons, and thus redistribution of local spotlights of activity in neocortical circuits, while preserving the balanced state of the whole network.